Bibliometric analysis for performance measurement in business, management and accounting subject area - Cvetkoska, Violeta; Eftimov, Ljupco (Journal of Engineering Management and Competitiveness (Online), 2021)
Based on our search in the Scopus data base with the phrases: "bibliometric analysis" and "performance measurement" and "business, management and accounting" in title - abstract - keywords we have not found any study considering this topic. Taking into account the importance of performance measurement in business, management and accounting we have conducted a bibliometric analysis in this area in the Scopus database. Our analysis covers the first 1,000 journal published articles with most citations and the period is 42 years (1978-2019). We provide analysis and visualization on distribution of articles per year, top journals, most cited articles, top authors, country-co-authorship as well as in depth keywords co-occurrence analysis by mining the abstracts. This study will serve as a starting point for researchers and practitioners interested in measurement of performance in business, management and accounting.